Peningkatan Fungsi Atensi dan Memori Jangka Pendek pada Wanita Dewasa Muda dengan Ansietas setelah Terapi Mewarnai - Moses A Krisnanda; Stella T Hasianna; Yenni Limyati (Universitas Kristen Maranatha, 2020)
Attention and memory are influenced by anxiety. This study aimed to analyze the effect of coloring therapy on the improvement of attention and short-term memory function in young adult women with anxiety. The analytic quasi-experimental method was used with pre-test and post-test design. The measured data were attention (Stroop test score) and short-term memory (Scenery Picture Memory Test / SPMT score). The subjects were 25 female university students with anxiety (Depression Anxiety Stress Scale / DASS-42 score ?8). This study showed the mean Stroop test scores of pre-test and post-test were 136.20 and 72.60 seconds subsequently, and the mean SPMT scores of pre-test and post-test were 17.88 and 20.92 subsequently. Wilcoxon's statistical analysis test with ?=0.05 showed a p-value of 0.000 for both the Stroop test and SPMT score (highly significant). We concluded that coloring therapy improved attention and short-term memory function in young adult women with anxiety. Keywords: coloring therapy, attention, short-term memory, cognitive, anxiety